2016
DOI: 10.1007/s10565-016-9369-2
|View full text |Cite
|
Sign up to set email alerts
|

Disruption of endolysosomal trafficking pathways in glioma cells by methuosis-inducing indole-based chalcones

Abstract: Methuosis is a form of non-apoptotic cell death involving massive vacuolization of macropinosome-derived endocytic compartments, followed by a decline in metabolic activity and loss of membrane integrity. To explore the induction of methuosis as a potential therapeutic strategy for killing cancer cells, we have developed small molecules (indole-based chalcones) that trigger this form of cell death in glioblastoma and other cancer cell lines. Here we report that in addition to causing fusion and expansion of ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
21
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 73 publications
5
21
0
Order By: Relevance
“…Cells undergoing methuosis initially exhibit massive vacuolization of macropinosomes and late endosomes. Our recent studies indicate that this is due to defective trafficking of late endosomes to lysosomes, with concomitant homotypic fusion of the affected vesicular compartments [5]. The defect in lysosome-directed trafficking also affects autophagic flux, with resultant accumulation of autophagosomes [5].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Cells undergoing methuosis initially exhibit massive vacuolization of macropinosomes and late endosomes. Our recent studies indicate that this is due to defective trafficking of late endosomes to lysosomes, with concomitant homotypic fusion of the affected vesicular compartments [5]. The defect in lysosome-directed trafficking also affects autophagic flux, with resultant accumulation of autophagosomes [5].…”
Section: Introductionmentioning
confidence: 99%
“…Our recent studies indicate that this is due to defective trafficking of late endosomes to lysosomes, with concomitant homotypic fusion of the affected vesicular compartments [5]. The defect in lysosome-directed trafficking also affects autophagic flux, with resultant accumulation of autophagosomes [5]. Ultimately, the integrity of the cell membrane is compromised and the vacuolated cells rupture in a manner reminiscent of necrosis.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Methuosis is a nonapoptotic form of cell death characterized by cell sprouting that induces a mutual fusion between different cells and the accumulation of vacuoles in the vesicles [20,21]. We investigated the possible molecular mechanisms through which EPS causes cell death via methuosis and found that previous studies have shown how RAS is related to methuosis [20][21][22].…”
Section: Discussionmentioning
confidence: 98%
“…Autophagy is the machinery of the intracellular degradation process, which is also the part of the intracellular membrane system and is linked to the endolysosomal pathway [51,53]. Furthermore, recent studies have been accumulating concerning a new type of cell death associated with large vacuoles, named methuosis, although it is thought Cytotoxicity that this type of cell death does not require caspases [54,55]. Some of the machineries mentioned above might be related to the cell death caused by TiNSs.…”
Section: Discussionmentioning
confidence: 99%